Peningkatan Keterampilan Berbicara Siswa Kelas XI SMA Negeri 1 Sigi Biromaru Melalui Metode Ceramah - Dedi Siswanto (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to improve the speaking skills of eleventh-grade students at SMA Negeri 1 Sigi Biromaru through the implementation of the lecture method. This research employed Classroom Action Research (CAR), conducted in two cycles, each consisting of planning, action implementation, observation, and reflection stages. The research subjects were 32 eleventh-grade students of SMA Negeri 1 Sigi Biromaru, while the object of the study was students’ speaking skills. Data were collected through observation, speaking skill tests, and documentation. The data were analyzed using descriptive qualitative and quantitative methods. The results of the study indicate an improvement in students’ speaking skills in each cycle. In the pre-cycle stage, the class average score was 68.2 with a mastery percentage of 31.25%. After the implementation of the lecture method in Cycle I, the average score increased to 74.6 with a mastery percentage of 56.25%. In Cycle II, the class average score increased significantly to 82.4 with a mastery percentage of 84.38%. These improvements were evident in aspects of fluency, confidence, clarity of pronunciation, and the organization of ideas. Therefore, it can be concluded that the planned and interactive application of the lecture method is effective in improving the speaking skills of eleventh-grade students at SMA Negeri 1 Sigi Biromaru.